The Effect of Work Flexibility on Employee Performance With Organizational Culture as a Mediation Variable at the Kutambaru Sub-district Office - Irwansyah; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The purpose of this study is to find out and analyze the influence of Work Flexibility on Employee Performance mediated by Organizational Culture on Employees of the Kutambaru District Office. This research was carried out at the Kutambaru District Office. The type of research is quantitative associative. The sample in this study is 15 employees of the Kutambaru District Office. The sampling technique in this study uses a saturated sample so that the entire population will be a sample of 15 people. The results of the study show that Work Flexibility does not have a significant influence on Employee Performance as shown by the T-Statistic value of 0.357 < 1.96 and the P Value of 0.721 > 0.05. In the effect of Work Flexibility on Organizational Culture, data on T-Statistics values were obtained from 2.594 > 1.96 and P-Value values of 0.010 < 0.05 or there was an influence of Work Flexibility on Organizational Culture. Organizational Culture has a significant effect on Employee Performance with a T-Statistic value of 2,459 > 1.96 with a P-Value of 0.014 < 0.05. In the indirect influence, the results show that Organizational Culture has a role as an intervening variable in explaining the relationship between Work Flexibility and Employee Performance of Kutambaru District Office. This shows that improvements in Work Flexibility can improve Organizational Culture, which ultimately contributes to improving the Performance of Employees of Kutambaru District Office.